Peran Implikasi Good Corporate Governance dalam Pendeteksian Fraudulent Financial Statement Menggunakan Fraud Hexagon Theory - aini, sarifa; Harto, Puji (Fakultas Ekonomi dan Bisnis Universitas Islam DR KH EZ Mutaqien, 2025)
Detecting fraudulent financial statements in Indonesia’s property, real estate, and construction sector during 2017–2023, this study adopts the Fraud Hexagon Theory with the moderating role of Good Corporate Governance (GCG). The six fraud elements are measured using the following proxies: personal financial need (pressure), effective monitoring (opportunity), auditor change (rationalization), director change (capability), CEO duality (arrogance), and political connection (collusion). GCG is examined as a moderator to assess whether it strengthens or weakens the relationship between these fraud factors and financial statement fraud. A total of 205 observations from 34 IDX-listed firms were analyzed using multiple linear regression and moderation analysis via SPSS version 26. The results show that none of the six fraud hexagon components have a significant direct effect on fraudulent financial statements. However, GCG is found to moderate and weaken the influence of political connections on financial fraud, though it fails to moderate other fraud elements. This suggests that while GCG can serve as a safeguard against politically driven fraud, it is not consistently effective across all fraud dimensions. Future research should refine fraud detection models by exploring alternative variables and enhancing the operationalization of fraud proxies within the Fraud Hexagon framework.